Let a 1 , a 2 , a 3 , … a 2 n , a 2 n + 1 be an arithmetic progression. If the sum of all the odd-numbered terms is 1 3 0 and the sum of all the even-numbered terms is 1 1 7 , what is 2 n + 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi there. Your solution is not correct. The difference in the two sums is 1 3 0 − 1 1 7 = ( a 2 n + 1 − a 2 n ) + ( a 2 n − 1 − a 2 n − 2 ) + . . . + ( a 3 − a 2 ) + a 1 = 2 n d + a 1 . And at the end, you assumed 2 4 7 is the last term of the sequence instead of the sum of the sequence.
If you start by assuming a 1 = 0 , then the number of terms is 1 9 , but the common difference is 9 1 3 .
Problem Loading...
Note Loading...
Set Loading...
The progression ends with an odd term a 2 n + 1 so the odd terms are one more than the even terms.
Calling "d" the common difference of the progression, the difference between the sums of odd and even terms equals to the difference between the last two terms:
a 2 n + 1 − a 2 n = [ a 1 + ( 2 n × d ) ] − [ a 1 + ( ( 2 n − 1 ) × d ) ] = d = 1 3 0 − 1 1 7 = 1 3
The total amount of the progression is 1 3 0 + 1 1 7 = 2 4 7
Being 247 a multiple of 13 ( 1 3 2 4 7 = 1 9 ) , we can easily say a 1 = 0 and 2 n + 1 = 1 9